Family violence, protection orders and systems abuse: views of legal practitioners. Issue 1 (2nd January 2020) - Reeves, Ellen
ABSTRACT: Family violence is a prominent public health issue in Australia, and in accordance with its gendered nature, women and children face significant risk. Knowledge of family violence is both multidisciplinary and continuously growing, yet explorations of the experiences of female 'perpetrators' remain limited. This article discusses research on the misidentification of female victim-survivors as predominant aggressors within the context of Victoria's family violence intervention order (FVIO) system, which was conducted through interviews with eight Melbourne-based legal practitioners. To date, understanding women's experiences of misidentification in the FVIO system has been left under-researched. Whilst there are multiple explanations for the misidentification of predominant aggressors within other jurisdictions, this paper is particularly concerned with the intersection between manipulative techniques employed by abusers and the FVIO system. The findings of this research suggest that male perpetrators may use the FVIO system to commit 'systems abuse' by encouraging police officers to apply for a FVIO against the genuine victim-survivor. It is argued that there is a strong need for a greater recognition of systems abuse within the police and the judiciary in order to prevent the FVIO system from serving as a tool of abuse readily available to perpetrators of family violence.